The Effect of Book Tax Gap, Cash Flow Volatility, Operating Cycle, and Financial Leverage on Earnings Persistence: The Moderating Role of Managerial Ownership - Rodiyah Kusuma Dewi; Dewi Indriasih; Teguh Budi Raharjo (Jurnal Wacana Ekonomi, 2026)
The volatile nature of earnings within the consumer cyclicals industry often mirrors the sector's acute vulnerability to macroeconomic shifts, casting doubt on the long-term viability of corporate financial performance. Sparked by a persistent lack of consensus in prior literature regarding what truly drives profit durability, this inquiry delves into the underlying mechanics of earnings persistence. The research centers on evaluating the influence exerted by the book tax gap, operating cash flow variance, the duration of the operating cycle, and financial leverage. To provide a deeper layer of analysis, managerial ownership is introduced as a moderating force to determine whether internal governance can tilt the relationship between these factors and earnings stability for firms listed on the Indonesia Stock Exchange between 2021 and 2025. Drawing from a quantitative dataset of 260 observations across 52 entities, the application of Moderated Regression Analysis (MRA) brought several critical insights to light. The data reveals that the discrepancy between accounting and taxable income the book tax gap actually serves as a positive catalyst, reinforcing the persistence of earnings. Conversely, a protracted operating cycle acts as a primary bottleneck, significantly eroding the stability of reported profits. Interestingly, neither the fluctuations in cash flow nor the weight of financial debt played a meaningful role in shaping earnings trajectories during this period. The moderating impact of managerial ownership proved highly targeted; it functioned exclusively to buffer the negative repercussions of a lengthy operating cycle. Ultimately, this study underscores that maintaining a resilient financial profile depends less on debt structures and more on the strategic alignment of fiscal reporting and the aggressive pursuit of operational efficiency.